Penegakan Hukum Piracy Dalam Hukum Internasional Dan Regional Asean Sebagai Upaya Pertanggungjawaban Negara - Dwi Cahyo, Imam (Faculty of Law, University of Mataram, 2025)
Maritime security is an important aspect in maintaining the economic, political, and social stability of a country, especially those with extensive sea areas. The threat of maritime crime, such as ship hijacking, can disrupt international trade activities, damage relations between countries, and endanger the safety of shipping. Therefore, collective efforts between countries are needed to eradicate ship hijacking crimes. In recent decades, ship hijacking crimes have increased in certain waters, both on the high seas (piracy) and in territorial waters (armed robbery against ships). This article discusses law enforcement in order to maintain maritime security at the international and ASEAN regional levels as protection for victims of piracy. This article evaluates how Indonesia, as a country that ratified UNCLOS 1982, faces the challenge of protecting its citizens from ship hijacking crimes. From various cases of ship hijacking that have occurred and involving Indonesian citizens, it shows the lack of effective control by the Indonesian government. Therefore, the Indonesian government is expected to be more proactive in preventing acts of piracy and armed robbery against ships in the future.